Viabilidade agroecológica de caixa de isopor® para colônias de abelhas Apis mellifera africanizadas pelo monitoramento de variáveis ambientais - Gasparotto, Bruna Figueiredo (2017)
Environmental variables such as temperature and relative humidity can affect the development of a colony, however bees use physiological and behavioral mechanisms for homeostasis. To evaluate the influence of environmental factors and the material used for the construction of Langstroth type boxes is fundamental for the best possible performance of the hive, in all factors, considering mainly the welfare of the bees, however, respecting the environment in which the activity Is installed. The experiment was carried out in the beekeeping sector of the Experimental Farm Iguatemi (FEI - PR), of the Animal Science Department of UEM. The objective was to monitor the temperature and relative humidity, every five minutes, during twelve days of March, evaluated in four periods of the day (1:00 a.m. to 6:00 a.m., 2:00 a.m. to 12 a.m., 3 a.m. to 6 a.m. And 4: 18h to 00h), from the years 2015 and 2016, colonies of Africanized Apis mellifera bees housed in wooden hives (3) and isopor® (3), through sensors, observing their performances. For statistical evaluation, analysis of variance (ANOVA) was performed and the means were compared by the Tukey test, at the 5% level of significance and the software used was STATISTICA 8.0. The results showed that there was no statistical difference between the materials in the period of 2015, with a mean temperature of 34.98ºC and a relative humidity of 60.22% (isopor®) and a mean temperature of 34.85ºC and the relative humidity of 58.20% (wood), inside the nest. In the period of 2016, the values average temperature of 35.22ºC and relative humidity of 58.28% (isopor®) and average temperature of 35.38ºC and the relative humidity of 59.96% (wood), inside the nest. There was a difference between the analyzed periods being consistent with the adaptation of the swarms during the periods during one day suggesting that the boxes of isopor® are apt for the beekeeping activity.